The bovine oviductal environment and composition are negatively affected by elevated body energy reserves - Natália Marins Bastos; Rodrigo Silva Goulart; Alessandra Bridi; Rosane Mazzarella; Luana Alves; Paola Maria da Silva Rosa; Ricardo de Francisco Strefezzi; Lindsay Baltel Paskoski; Ricardo Perecin Nociti; Juliano Rodrigues Sangalli; Schaienni Fontoura Saldanha; Camila Azzolin de Souza; et al. (PLoS ONE, 2025)
To analyze the effects of high body energy reserve (BER) within the oviductal environment and its composition, Nellore cows were fed two different nutritional plans to obtain animals with moderate BER (MBER) and high BER (HBER). After obtaining the groups with different BERs, all animals were subjected to oestrus synchronization and artificial insemination, and 120 hours after ovulation induction, the cows were slaughtered, the reproductive tract was removed, and the ipsilateral oviduct to the corpus luteum was collected and dissected. Analyses were performed only for animals that had an 8-cell embryo in the isthmus. After embryo identification, we evaluated the molecular profiles of extracellular vesicles from oviductal flushing (OF-EVs) and luminal epithelial cells (OV-Cell) and performed histomorphological analysis of oviductal tissue from the ampullary and isthmic oviductal regions. The HBER group presented higher concentrations of ampullary extracellular vesicles (AMP-EVs) and larger sizers of isthmic extracellular vesicles (IST-EVs). The miRNA profile of AMP-EVs showed that the differentially expressed miRNAs were predicted to regulate pathways associated with cell growth, migration, differentiation and metabolism, with the HBER group being more susceptible to insulin modulation. The MBER animals showed greater ampullary vascularization than the HBER animals did. Additionally, the miRNA profile and differential gene expression (DEG) data obtained for ampullary (AMP-Cell) and isthmic (IST-Cell) luminal epithelial cells revealed pathways related to insulin metabolism. Thus, elevated BER may lead to oviductal insulin resistance, affecting normal functioning and, probably, embryo metabolism during early development, thus impacting gestational rates in these animals.